Simultaneous saccharification and fermentation of ethanol production by using saccharomyces cerevisiae - Muhammad Naimmi, Ismail (Universiti Malaysia Sarawak (UNIMAS), 2012)
Liquefied sago starch (LSS), which acts as a substrate for the production of the ethanol was studied in batch fermentation process involving Saccharomyces cerevisiae CSI-1. This research focuses on the relevant conditions for optimum ethanol production by using liquefied sago starch with addition 10mg/L of calcium pantothenate (vitamin B5) under controlled temperature to assess their effects on ethanol production. The optimum production of ethanol by addition calcium pantothenate was recorded at 24 hr (5.58 g/L) and (5.71 g/L) without the addition of calcium pantothenate at 9 hr. These preliminary results proved the feasibility of liquefied sago starch as a potential substrate for ethanol production by using Saccharomyces cerevisiae CSI-1.